Data from: Geographic variation in age structure and longevity in the nine-spined stickleback (Pungitius pungitius) - DeFaveri, Jacquelin; Shikano, Takahito; Merilä, Juha (Zenodo, 2015)
Variation in age and size of mature nine-spined sticklebacks (Pungitius pungitius) within and among 16 Fennoscandian populations were assessed using skeletochronology. The average age of individuals in a given population varied from 1.7 to 4.7 years. Fish from pond populations were on average older than those from lake and marine populations, and females tended to be older than males. Reproduction in marine and lake populations commenced typically at an age of two years, whereas that in ponds at an age of three years. The maximum life span of the fish varied from 3 to 7 years. Mean body size within and among populations increased with increasing age, but the habitat and population differences in body size persisted even after accounting for variation in population age (and sex) structure. Hence, the population differences in mean body size are not explainable by age differences alone. As such, much of the pronounced intraspecific variation in population age structure can be attributed to delayed maturation and extended longevity of the pond fish. The results are contrasted and discussed in the context of similar data from the three-spined stickleback (Gasterosteus aculeatus) occupying the same geographic area. Merila_dryad Sex, age and standard length of all specimens used in the study